2018
DOI: 10.2176/nmc.oa.2017-0167
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Glioblastoma: Is There a Role for Epilepsy?

Abstract: The prognostic relevance of epilepsy at glioblastoma (GBMs) onset is still under debate. In this study, we analyzed the value of epilepsy and other prognostic factors on GBMs survival. We retrospectively analyzed the clinical, radiological, surgical and histological data in 139 GBMs. Seizures were the presenting symptoms in 50 patients out of 139 (35.9%). 123 patients (88%) were treated with craniotomy and tumor resection while 16 (12%) with biopsy. The median overall survival was 9.9 months from surgery. At u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
5
15
1
Order By: Relevance
“…SP was significantly associated with increased OS independent of age, sex, tumor location, and size in the systematic review of Phan 2018 19 . However, we and others found that OS was not dependent on clinical seizure presentation 10,29,30 despite smaller tumor size in the SP group. We did find that Grade III SP patients had significantly greater OS.…”
Section: Overall Survivalcontrasting
confidence: 60%
See 1 more Smart Citation
“…SP was significantly associated with increased OS independent of age, sex, tumor location, and size in the systematic review of Phan 2018 19 . However, we and others found that OS was not dependent on clinical seizure presentation 10,29,30 despite smaller tumor size in the SP group. We did find that Grade III SP patients had significantly greater OS.…”
Section: Overall Survivalcontrasting
confidence: 60%
“…Tumor location matters in SP, but the methods used to ascertain tumor location strongly vary across groups making comparisons and conclusions difficult. Many 22,25,28,29 studies reported highest incidences for frontal lobe tumors are associated with SP in both univariate and multivariate analyses. While Lee found temporal lobe tumors in LGG were twice as likely for SP but not true in HGG 24 .…”
Section: Tumor Location Lobes and Lateralitymentioning
confidence: 99%
“…Seizures can occur either at initial diagnosis or result from recurrence of the disease. Although they reduce the patient quality of life, seizures as a symptom are positively correlated to longer survival in glioblastoma patients [60][61][62]. However, in cases where there is a longer delay between epileptic seizures as a symptom and surgical resection of tumor, this correlation does not seem to be significant [62,63].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 99%
“…Several previous reports have addressed the association between SAO occurrence and glioblastoma survival, both with positive 2 , 4–8 and negative 9–17 results. The majority of recent studies has specifically focused on the role of antiepileptic drugs (AED) on the survival effect of SAO.…”
mentioning
confidence: 99%